2018
DOI: 10.1136/bmjopen-2017-019250
|View full text |Cite
|
Sign up to set email alerts
|

Cohort profile: ‘Centenari a Trieste’ (CaT), a study of the health status of centenarians in a small defined area of Italy

Abstract: PurposeCentenarians, a segment of the population which some 50 years ago comprised only a few individuals, now count thousands in many countries, and demographic projections forecast that this growth will continue. The study of this new population will give us new information on extreme longevity and help prepare for their health and social needs. The aim of the Centenari a Trieste study is to describe the health and health service use by centenarians, with specific focus on cognitive status.ParticipantsThis i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
8
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 61 publications
2
8
0
Order By: Relevance
“…Apart from in Switzerland, the share of institutionalised centenarians in our sample agreed with the findings of several studies (from 42.1% in Portugal to 53.7% in Canada) 9 10 13 14. However, other works disclosed proportions above 60%, and a study based on European census data revealed considerable geographical variations, with percentages ranging from 10% to 90% 6 15 16. The Swiss exception observed in 5-COOP is consistent with its more substantial proportion of elders living in institutions, as reported in OECD statistics, and matches the greater numbers of staff and long-term care beds found there.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…Apart from in Switzerland, the share of institutionalised centenarians in our sample agreed with the findings of several studies (from 42.1% in Portugal to 53.7% in Canada) 9 10 13 14. However, other works disclosed proportions above 60%, and a study based on European census data revealed considerable geographical variations, with percentages ranging from 10% to 90% 6 15 16. The Swiss exception observed in 5-COOP is consistent with its more substantial proportion of elders living in institutions, as reported in OECD statistics, and matches the greater numbers of staff and long-term care beds found there.…”
Section: Discussionsupporting
confidence: 91%
“…Disparities exist within countries too, as in Sweden, where municipalities are responsible for organising meals-on-wheels and pursue varying policies 20. In contrast, centenarians’ experiences of acute care hospital stays overnight differed little between countries and were similar to other observations made in Europe, Canada and Australia (ranging from 10.9% to 22.1%) 6 10 14 15. Studies conducted in England and the USA have revealed annual hospital admission rates for centenarians superior to 50%, suggesting that all the 5-COOP countries had low hospitalisation rates by international standards 21 22.…”
Section: Discussionmentioning
confidence: 66%
See 1 more Smart Citation
“…The protocol of the CaT study to obtain, after informed consent, demographic, anamnestic, clinical and lifestyle data from the subjects enrolled in the study was already published [ 36 ] .…”
Section: Methodsmentioning
confidence: 99%
“…The study was carried out in Trieste, Italy, which has a large population showing longevity (Tettamanti & Marcon, 2018). In Italy, a National Health System exists with autonomous local health authorities (LHAs).…”
Section: Methodsmentioning
confidence: 99%